Time resolved cryogenic cooling analysis of the Cornell Injector Cryomodule. Issue 1 (November 2015) - Eichhorn, R; Markham, S; Smith, E; Quigley, P
Abstract: Managing parallel cryogenic flows has become a key challenge in designing efficient and smart cryo-modules for particle accelerators. In analysing the heating dynamics of the Cornell high current injector module a computational tool has been set-up allowing time resolved analysis and optimization. We describe the computational methods and data sets we have used, report the results and compare them to measured data from the module being in good agreement. Mitigation strategies developed on basis of this model have helped us in pushing the operational limitations.